AI Chatbot Innovation – Leading toward Consumer Satisfaction, Electronic Word of Mouth and Continuous Intention in Online Shopping - Butt, Asad Hassan; Ahmad, Hassan (Journal of Telecommunications and the Digital Economy, 2023)
AI-powered chatbots have emerged as influential tools in the realm of online shopping, effectively driving digital users toward heightened satisfaction, sustained usage intention and positive electronic word of mouth (e-WOM). This research delves deep into the intricate behavioural dynamics that consumers exhibit in their interactions with AI chatbots. A comprehensive online survey, encompassing 554 respondents who willingly engaged with AI chatbots, was conducted, with a focus on established frameworks like the information systems success (ISS) model, the technology acceptance model (TAM), engagement, and the elicitation of pleasurable feelings. The study’s findings underscore the pivotal role AI chatbots play in elevating user satisfaction and, in turn, predicting positive outcomes. These insights hold immense value for brand managers, offering a nuanced understanding of Indian online shoppers’ behaviour. Furthermore, the study highlights the significant impact of e-WOM generated by AI chatbots within the online shopping domain, further solidifying their role as essential components of digital services in the contemporary landscape. As digital services continue to shape and define modern business operations, AI chatbots have emerged as critical facilitators in enhancing the satisfaction of digital users, making them indispensable for businesses seeking to thrive in the digital realm.